2018
DOI: 10.1016/s0140-6736(18)30313-1
|View full text |Cite
|
Sign up to set email alerts
|

Intervention strategies to improve nutrition and health behaviours before conception

Abstract: The nutritional status of both women and men before conception has profound implications for the growth, development, and long-term health of their offspring. Evidence of the effectiveness of preconception interventions for improving outcomes for mothers and babies is scarce. However, given the large potential health return, and relatively low costs and risk of harm, research into potential interventions is warranted. We identified three promising strategies for intervention that are likely to be scalable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
329
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(338 citation statements)
references
References 90 publications
9
329
0
Order By: Relevance
“…Studies in Taiwan and the United States have found an increased birthweight in subsequent babies from mothers that were supplemented in micronutrients/macronutrients for several months after the birth of their first baby. Our results support preventive interventions started prior to conception or even early in pregnancy to improve nutritional status of women such as supplementation or preventive strategies against malaria and helminthic diseases, which could influence nutritional status …”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Studies in Taiwan and the United States have found an increased birthweight in subsequent babies from mothers that were supplemented in micronutrients/macronutrients for several months after the birth of their first baby. Our results support preventive interventions started prior to conception or even early in pregnancy to improve nutritional status of women such as supplementation or preventive strategies against malaria and helminthic diseases, which could influence nutritional status …”
Section: Discussionsupporting
confidence: 73%
“…According to WHO standards, 22% of infants were affected by stunting at 12 months of age with a higher risk in infants born from mothers with underweight before conception. These results reinforce the need for improving maternal nutritional conditions as early as in the preconception period …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…For this reason, many nutrition interventions focus on improving maternal nutrition during pregnancy and/or child nutrition during the first 2 years. More recently, the preconception period has received increasing attention as another critical, and generally overlooked, window for improving maternal nutrition and child outcomes (Barker et al, 2018;De-Regil, Harding, & Roche, 2016;Stephenson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…“Preconception” can be construed narrowly, for instance, as the time period when pregnancy is planned, or broadly, as any point in the life span prior to pregnancy . Exposures from both time periods have been found to affect pregnancy and infant health (eg folic acid supplementation or adverse childhood experiences).…”
Section: Introductionmentioning
confidence: 99%